The Mastigitae genus †Baltostigus in Upper Eocene Rovno amber (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł; Perkovsky, Evgeny (Zootaxa, 2019)
Three species of the extinct Eocene genus Baltostigus (Mastigitae: Baltostigini) were known in Baltic amber from Poland, Lithuania and Russia. In Rovno amber, although it was relatively well-studied, only one Mastigitae genus and species was recorded, belonging to Leptochromini. We report the occurrence of Baltostigus in the area of the present day Ukraine during the Eocene, on the basis of three inclusions in Rovno amber. One specimen belongs to a newly described species, Baltostigus substriatus sp. n.; two specimens are putatively identified as Baltostigus cf. horribilis, and may represent females of this species. However, further study based on more specimens is necessary to clarify the identity of these specimens.